Relationships between parenting style, parental school involvement, academic self-efficacy, emotional intelligence, academic engagement, and academic achievement among adolescent - Dehyadegar, Elham (2012)
Factors influencing students' achievement or failure have always been a basic issue in education; however, despite the extensive line of research conducted and a large amount of budgets spent, there are still huge numbers of students who experience failure in academic performance each year. However, the study on relationship between maternal parenting style, maternal school involvement, academic self-efficacy, emotional intelligence, academic engagement with academic achievement have received little attention in Iran. Thus, the current research is essential and necessary. The main purpose of this study is to determine the relationships between maternal factors (maternal parenting style and maternal school involvement), individual characteristics (academic self-efficacy, emotional intelligence, and academic engagement) and academic achievement among adolescents in Sirjan-Iran. This study utilized a quantitative approach and correlation research design. Respondents of the study consisted of 382 male and female high school students who were identified by proportional stratified random sampling technique. Instruments for data collection included Parent Authority Questionnaire (Buri, 1991), Paulson’s Parental Academic Involvement Questionnaire (1994), Morgan- Jink Academic Self-efficacy Questionnaire (1999), Shutte’s Emotional Intelligence Questionnaire (1998), and Short, Fleming, Guiling, and Roper’s Academic Engagement Questionnaire (2002). All the instruments used in this study were highly reliable. Descriptive, bivariate, and multivariate statistics were used in data analysis. The results of the Pearson correlation analysis showed that age of the respondents, family income, maternal authoritative and permissive styles, maternal school involvement, academic self-efficacy, academic engagement, and emotional intelligence were significantly related to academic achievement. In addition, maternal authoritative and permissive styles, maternal school involvement, academic self-efficacy, and emotional intelligence were significantly related to academic engagement. The result of the t-test showed that female respondents had significantly higher academic achievement compared to male respondents. The Hierarchical Regression Analysis showed that parents’ education, adolescents’ gender, maternal school involvement, academic self-efficacy, academic engagement, and emotional intelligence were significant contributors of academic achievement. Academic engagement emerged as the strongest predictor in adolescents’ academic achievement. The present study also found that academic engagement fully or partially mediates the relationships between all the independents (except maternal authoritarian style) variables with academic achievement among respondents. The findings of the present study highlighted the importance of maternal and personal factors in enhancing academic performance of school-going adolescents in Sirjan-Iran. However, the contributions of aforementioned variables in academic achievement are indirect through academic engagement. The nature of relationships between the independent variables, academic engagement as mediator and academic achievement implied that academic performance of adolescents can be improved if they show their commitment by engaging themselves more seriously in academic or school related activities.